Phenotypes of trypsin- and collagenase-prepared bovine corneal endothelial cells in the presence of a selective Rho kinase inhibitor, Y-27632 - Su, Chien-Chia (Mol Vis, 2015)
PURPOSE: To optimize isolation of viable bovine corneal endothelial cells (BCECs), we evaluated the effectiveness of various preparation protocols. This entailed comparing the effects of collagenase A and trypsin in the presence and absence of a Rho kinase inhibitor, Y-27632, on proliferation and tight junctional and cytoskeletal integrity during their expansion. METHODS: 5-bromo-2'-deoxyuridine (BrdU) incorporation evaluated cell proliferation. Western blot analysis evaluated F-actin, zonule occludin, and ZO-1 associated nucleic acid binding protein (ZONAB) and RhoA expression. Rho A pulldown assay evaluated Rho A activity. RESULTS: In the trypsin (TrypLE)-prepared BCECs, BrdU incorporation decreased whereas nuclear ZONAB expression increased and became stable from day 3 to 7. In contrast, in the collagenase-A-prepared BCECs, we observed preserved ZO-1 integrity, invariant nuclear ZONAB expression, and dense cortical F-actin expression, and BrdU incorporation was invariant from days 1 to 7. Y-27632 did not increase BrdU incorporation and nuclear ZONAB expression in the TrypLE-prepared and the collagenase-A-prepared BCECs. Moreover, Y-27632 increased irregular cellular morphology and downregulated the expression of ZO-1 in the collagenase-A-prepared BCECs from days 1 to 7. Y-27632 inhibited RhoA activation irrespective of whether the cells were isolated with trypsin or collagenase A. CONCLUSIONS: It is preferable to isolate BCECs with collagenase A and expand them without Y-27632. With this protocol, proliferative activity and tight junctional and cytoskeletal integrity are better preserved than if trypsin is used in the presence or absence of Y-27632.